First measurement with a new setup for low-energy Coulomb excitation studies at INFN LNL. (7th June 2017) - Rocchini, M; Hadyńska-Klȩk, K; Nannini, A; Valiente-Dobón, J J; Goasduff, A; Testov, D; John, P R; Mengoni, D; Zielińska, M; Bazzacco, D; Benzoni, G; Boso, A; et al.
Abstract: A new segmented particle detector, SPIDER, has been designed to be used as an ancillary device with the GALILEO γ -ray spectrometer, as well as with other multi-detector γ -ray arrays that will be available at LNL in the future (e.g. AGATA). To commission the SPIDER-GALILEO experimental setup, a multi-step Coulomb excitation experiment was carried out with a 240 MeV beam of 66 Zn produced by the Tandem-XTU accelerator at INFN Laboratori Nazionali di Legnaro. The measured particle and γ -ray spectra are compared with the results of detailed GEANT4 simulations which used the Coulomb excitation cross sections, estimated with the computer code GOSIA, as an input. The preliminary results indicate that precise transition probabilities will be obtained which are essential for solving discrepancies reported in the literature for this nucleus.